1996
DOI: 10.1590/s0034-89101996000200002
|View full text |Cite
|
Sign up to set email alerts
|

Estudo dos flebotomíneos (Diptera, Pychodidae), em área de leishmaniose tegumentar, no Estado de Mato Grosso do Sul, Brasil

Abstract: ResumoDesenvolveram-se estudos sobre flebotomíneos em área de leishmaniose tegumentar, fazenda Boa Sorte, Município de Corguinho, Mato Grosso do Sul, Brasil, com vistas a incriminar vetor dessa parasitose. No início dos estudos, encontravam-se bem preservados vários tipos da cobertura vegetal primitiva, com predomínio de cerrado e cerradão, denominado localmente de "croa". Decorridos quatro meses, parte significativa da "croa" e do cerrado foi queimada para transformação em áreas de pastagens. Durante julho/19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
50
2
28

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 14 publications
13
50
2
28
Order By: Relevance
“…As regards the partial nocturnal rhythm of N. whitmani in the PEMD: it is similar to that observed by Galati et al (1996), presenting peaks between 8:00 pm and 9:00 pm, suggesting that this period is the one which presents the highest risk of infection. In the São Paulo State its most intense activity occurred during the 3 rd hour after dusk (MAYO et al, 1998), whereas in the north of Paraná State, it occurred from 9:00 pm to 10:00 pm (TEODORO et al, 1993) and in the Bandeirantes municipality in the same state, from 8:00 pm to 10:00 pm (MASSAFERA et al, 2005).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As regards the partial nocturnal rhythm of N. whitmani in the PEMD: it is similar to that observed by Galati et al (1996), presenting peaks between 8:00 pm and 9:00 pm, suggesting that this period is the one which presents the highest risk of infection. In the São Paulo State its most intense activity occurred during the 3 rd hour after dusk (MAYO et al, 1998), whereas in the north of Paraná State, it occurred from 9:00 pm to 10:00 pm (TEODORO et al, 1993) and in the Bandeirantes municipality in the same state, from 8:00 pm to 10:00 pm (MASSAFERA et al, 2005).…”
Section: Discussionsupporting
confidence: 77%
“…In Corguinho municipality, Mato Grosso do Sul State, the seasonal pattern of L. whitmani, with peaks in the winter (GALATI et al 1996), was similar to that found in the PEMD. The decrease in the number of specimens of L. whitmani captured in the summer and autumn was related to higher atmospheric humidity and the moderate winds when the captures were made, factors already recognized as interfering in the activity of the sandflies.…”
Section: Discussionsupporting
confidence: 64%
“…Analysis of the results showed that, similar to other areas of ACL occurrence in the State of Mato Grosso do Sul 4,40,41 , disease transmission is associated with wild vector patterns and with human exposure to vectors in their natural habitat.…”
Section: Discussionmentioning
confidence: 65%
“…A rich variety of sandfly species in different ecotopes has been identified in several ecological studies conducted in this state. These studies have indicated new species or have reinforced the role that some of them play in the transmission of leishmaniasis to the population of different municipalities, contributing to current understanding of the epidemiology of these diseases in the state [1][2][3][4][5][6] .…”
Section: Sand Fly Captures With Disney Traps In Area Of Occurrence Ofmentioning
confidence: 99%
“…Estimates of the infection rate in phlebotomines based on dissection of the insects are frequently carried out. Infection rates obtained by this method range from 0 to 9% 1,9,11,19 but are usually in the region of 0.2% 9,10,14,17,18 .…”
Section: Introductionmentioning
confidence: 98%